Pacto Nacional pela Alfabetização na Idade Certa (PNAIC): a educação como legitimação e dominação social - Martins, Maria Artemis Ribeiro (2016)
This dissertation presents a critical analysis of the National Pact for Literacy in the Right Age (Pacto Nacional pela Alfabetização na Idade Certa) - PNAIC, policy established in response to the requirements of the World Bank Group for Brazilian educational system, and has as main objective to find it as a legitimating mechanism of the social domination. This is a documental and bibliographic research supported by the marxist theoretical axis. We opted for the synthesis of multiple determinations that grants us the historical and dialectical materialism, as well as in Marx, both the expository path of this investigation as the mentioned above complex will be guided by our object. The logic of this approach is based on the concept of education as an investment in men, i.e. in the formation of human capital and intellectual capital, based on the ideology of equal opportunities, that promotes in people the belief that everyone, regardless of their social background, are able to enter equitably in the individual pursuit of the development of their skills and abilities and thus to ascend socially. This rise - albeit partial, limited and based on expanding access to consumer goods through indebtedness programs - endorses the naturalization of inequality, the class change fiction, the compliance with the objective conditions of existence and the detachment of the class struggle, therefore, for the legitimation and social domination. Considering the role and the paths taken by international agencies on the educational field in Brazil, regarding the education policies in the international scope that emerged during the post-war decades, continuing on at the turn of the twenty-first century and appeared in the Brazilian scene in early 2000`s, alongside the theory of equal opportunities by François Dubet - an ideology that legitimizes and naturalizes the inequalities, the Brazilian education is here conceived in the context of capitalist sociability and class struggle, influenced by the nuances of the international economy and politics. Despite the unveiled limits and the need of class organs intermediating, we conclude that education (with the educational systems and schools) has an essential role in the socialization of the knowledge historically constructed and represents a moment of great importance for the development of a proletariat consciousness with the merge between the theoretical and practical spheres of the human existence. Therefore, it can assist in working class struggle for emancipation.